Mechanical, chemical and biological properties of PLA 3D printer: A systematic review (Research, Society and Development, 2023)
The aim of this systematic review is to evaluate, through the in vitro studies included, whether PLA has mechanical, chemical and biological properties that enable its clinical use in dentistry. An electronic search was carried out in the Pubmed, Science Direct, Embase and Scopus databases containing the terms ''polylactic acid'', ''3D printing'',''biomaterials'',''dental materials'', dental prosthesis and dentistry. The objective of the inclusion criteria was to cover articles written and published in English that focused on the use of PLA in the field of dental materials and biomaterials printed using the 3D method. Any articles that did not focus on the study of PLA polymer, as well as systematic reviews, book chapters, abstracts, letters and conference articles were excluded. 1814 references were found, which after applying the exclusion criteria resulted in the final inclusion of 13 articles for the review. Based on the studies included in this systematic review, it is possible to conclude that 3D printed PLA used as a dental material and biomaterial presents favorable mechanical, chemical and biological properties that indicate its potential clinical use.